A gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies and its preparation method and application
The surface energy of gold rods is regulated by thiol ligand, and the gold rod/cubous oxide Janus structure is formed, which solves the problems of charge accumulation and limited photocatalytic activity in the gold/cubous oxide core-shell structure, and achieves efficient photocatalytic performance improvement. The control ability of morphological diversity and the photocatalytic performance are significantly improved.
Patent Information
- Application Number
- CN202211150506.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The existing gold/cubous oxide core-shell structures have problems with excessive recombination and charge accumulation of photoexcited charges in photocatalysis, resulting in limited catalytic activity and lack of effective synthesis control methods.
By using small molecule thiol ligand to adjust the surface energy of the gold rod, the Janus structure of the gold rod/cubic acid structure is achieved, and the surface energy of the gold rod is regulated by using thiol ligand to grow island-shaped copper oxide, forming hot dog shape, dumbbell shape, and hammer Janus structure with different shapes, such as shape, improves charge separation efficiency and photocatalytic performance.
The photocatalytic performance of the gold rod/cubous oxide Janus structure is significantly improved. Compared with the traditional core-shell structure, the photocurrent is enhanced, and the photocatalytic efficiency is at least twice that of the core-shell structure. The material is simple and easy to obtain, the operation is gentle, and it has Broad application prospects.
Smart Images

Figure CN115945682B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a technology for growing semiconductors on a metal surface modified by mercapto ligands to obtain some composite nano materials with Janus structures, belonging to the technical field of nano material preparation. Background Art
[0002] For a long time, the ecological environment pollution and extreme climate disasters caused by greenhouse gases in the production and use of fossil energy have seriously threatened human survival and sustainable development. Solar energy has become the best alternative energy to fossil energy because of its clean and inexhaustible characteristics, and semiconductor photocatalytic materials are an effective way to utilize solar energy.
[0003] Based on the defects of poor hole mobility and high recombination rate of single semiconductor materials, combining semiconductors with plasmonic metal nanoparticles (such as gold, silver and copper) is an effective way to promote charge separation and interfacial charge transfer, thereby extending the lifetime of carriers involved in photocatalysis. In addition, plasmonic metals can further expand the light absorption of catalysts, which is due to the surface plasmon resonance effect, and is of great significance to improving photocatalytic performance. The preparation and performance research of metal / semiconductor composite photocatalyst nanomaterials is an important direction of photocatalytic materials. As a typical representative of P-type semiconductors, cuprous oxide (Cu 2 O), has the advantages of good crystallinity, good absorption of visible light, low toxicity and low cost, so gold / cuprous oxide is often used as a model material and widely studied. According to the applicant's understanding, from the current research progress of cuprous oxide, the composite of gold and cuprous oxide is mainly achieved through two methods.
[0004] The first method is to deposit gold particles on the surface of cuprous oxide (ACS Appl. Mater. Interfaces 2014, 6, 14, 10958-10962; Nanoscale Res Lett, 2019, 14, 63), which acts as an absorber of visible light and an accelerator of electron transfer. However, the large number of interface defects in the structure always act as recombination sites for photogenerated electrons and holes, which greatly reduces the photocatalytic activity.
[0005] The second way is to construct a core-shell structure of gold particles and cuprous oxide (Nanoscale 2016, 8, 965-972; J.Am.Chem.Soc.2011, 133, 1052-1057), which is the most popular hybrid configuration, in which the interfacial charge transfer between gold and cuprous oxide can be promoted to a certain extent. However, the results show that core-shell photocatalysts all show excessive recombination of photoexcited charges, usually due to the following reasons: 1) Metal / semiconductor hybrids are of great significance in photocatalysis because their catalytic activity can be significantly improved by the formation of Schottky barriers. However, in the core-shell structure, its advantages are greatly limited, because the complete coating of the gold core by the cuprous oxide shell can only use the charges on the surface of the semiconductor shell for photocatalytic reaction, and the opposite charges accumulate in the metal core. Therefore, the surface reaction of cuprous oxide and the charge accumulation of the gold core cannot continue forever. When the limit is reached, the photocurrent will decrease rapidly; 2) There will be a large resistance in the long-range electron migration process from the core to the surface catalytic active center, and it is easy to recombine with holes, resulting in a significant reduction in the reduction reaction ability. Therefore, the core-shell hybrid structure greatly limits the performance of the gold / cuprous oxide photocatalytic performance. Because gold and cuprous oxide have good lattice matching and material compatibility, only core-shell structures of various morphologies can be formed, but there is currently no strong control method to break through this synthetic barrier. Summary of the invention
[0006] The technical problem solved by the present invention is that defects existing between material interfaces can significantly change the interface energy. The present invention provides a strategy based on interface energy regulation, which utilizes small molecule thiol ligands to regulate the surface energy of gold seeds, and achieves a breakthrough in the transformation of the gold rod / cuprous oxide core-shell structure to a Janus structure. More importantly, by continuously regulating the surface energy of the gold seed by simply changing the amount of ligand, a series of continuously changing Janus structures (hot dog shape, dumbbell shape, hammer shape) are obtained, showing a regulation power that cannot be achieved by traditional methods, which is in sharp contrast to the traditional hybrid structure synthesis that mainly depends on the nature of the material. Thanks to the improvement in charge separation efficiency brought about by the physical separation of the Janus structural units and the surface plasmon resonance of the gold rod, the photocatalytic performance of the gold rod / cuprous oxide Janus structure has been significantly improved.
[0007] In order to solve the above technical problems, the technical solution proposed in the present invention is: different amounts of thiol ligand AMBI (5-amino-2-mercaptobenzimidazole) are used to adjust the surface energy of gold nanorods with different aspect ratios by incubation, and then added to an aqueous solution of surfactant SDS sodium dodecyl sulfate, different amounts of cuprous oxide precursors, sodium hydroxide and reducing agent hydroxylamine hydrochloride for reaction, so that island-shaped cuprous oxide grows on the surface of the gold rod, and a series of gold rod / cuprous oxide Janus structure nanomaterials with different morphologies are obtained.
[0008] Preferably, the preparation method of the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies can be carried out in the following steps:
[0009] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods with different aspect ratios were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0010] (2) Under high-speed vortex oscillation, different amounts of thiol ligand AMBI (5-amino-2-mercaptobenzimidazole) were injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0011] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution of different concentrations, the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, Janus nanostructured materials with different morphologies of gold rods / cuprous oxide can be obtained.
[0012] Preferably, the aspect ratio of the gold rod used in step 1 may be 4-6.
[0013] Preferably, the amount of the thiol ligand AMBI (1 mM) used ranges from 2 μL to 6 μL.
[0014] Preferably, the concentration of 0.6 mL of copper chloride in step (2) ranges from 2 mM to 6 mM.
[0015] Preferably: comprising the following steps:
[0016] (1) synthesizing a gold rod with an aspect ratio of 4, a length of 80 nm, and a diameter of 20 nm. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0017] (2) Under high-speed vortexing, 4 μL of 1 mM thiol ligand AMBI was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60°C for 2 h, and then allowed to stand to room temperature;
[0018] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution 2mM, the solution in step 2, 0.25mL sodium hydroxide solution 1M and 0.1mL reducing agent hydroxylamine hydrochloride solution 200mM, after standing and reacting at room temperature for 15min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material can be obtained.
[0019] Preferably, the molar ratio of the thiol ligand AMBI (5-amino-2-mercaptobenzimidazole) to the reducing agent hydroxylamine hydrochloride is 1-3:10000.
[0020] Preferably, the molar ratio of the cuprous oxide precursor solution to the sodium hydroxide solution is 3 to 9:625.
[0021] In order to solve another technical problem of the present invention, a technical solution is proposed: a gold rod / cuprous oxide Janus structure nanomaterial prepared by any of the methods described in item 1.
[0022] In order to solve another technical problem of the present invention, another technical solution is proposed: application of the gold rod / cuprous oxide Janus structure nanomaterial prepared by the method, characterized in that it can be used for photocatalytic materials.
[0023] Beneficial Effects
[0024] In our previous work, we successfully prepared Janus gold spheres / cuprous oxide nanostructures from spherical gold seeds (Angew. Chem. Int. Ed. 2020, 59, 22246-22251). It was proved that the Janus structure is significantly superior to the core-shell structure in preventing charge accumulation and promoting charge separation. Here, we combined the regulation of interface energy with the crystal plane, modified different crystal planes on the gold rods with thiol ligand molecules, and used the difference in binding force of the ligands on different crystal planes to regulate the distribution density of the ligands. We obtained a series of Janus structures of gold rods / cuprous oxide with continuously changing morphologies, which reflects the diversity of the control of the interface energy structure by thiol ligands. It is worth noting that the system can make full use of the surface plasmon resonance effect of the gold rods (absorption in the visible light region), so that the structural materials can use solar energy more efficiently.
[0025] The invention relates to a technology for controlling the growth of island-shaped cuprous oxide on the surface of a gold nanorod in a solution phase by a small molecule thiol ligand, and obtaining nanoparticles (hot dog shape, dumbbell shape, hammer shape) of a gold rod / cuprous oxide Janus structure with continuously changing morphology, novel structure, high uniformity, high repeatability, and adjustable size of cuprous oxide and aspect ratio of the gold rod. The physical separation of metal and semiconductor structural units in the Janus structure enables both materials to have exposed surfaces, and while having the advantages of a core-shell structure, there is no problem of charge accumulation. The nanomaterial finally obtained can be directly used for photocurrent testing, and has a significant charge separation efficiency compared to a core-shell structure. Thanks to the surface plasmon resonance absorption of the gold rod in the absorption of visible light, the photocatalytic performance of the gold rod / cuprous oxide Janus structure is significantly higher than that of the gold ball / cuprous oxide Janus structure. The raw materials required by the invention are simple and easy to obtain, the experimental conditions are mild, the operation process is simple, the toxicity is low, and there is a broad application prospect in the field of photocatalysis.
[0026] Compared with the gold rod / cuprous oxide core-shell structure, the gold rod / cuprous oxide hotdog-shaped, hammer-shaped, and dumbbell-shaped Janus structures all show obvious photocurrent enhancement in the ratio of 1:2:4:20, which is due to the physical separation of gold and cuprous oxide.
[0027] From the hot dog shape to the hammer shape and dumbbell shape of the Janus structure, the photocurrent shows a trend of gradual strengthening, which is most likely the influence of the strength of the Schottky effect. Gold / cuprous oxide is used as the photocathode material. The photogenerated electrons generated by cuprous oxide are transferred to the surface of the gold rod to participate in the water reduction reaction to release hydrogen. Therefore, more cuprous oxide is coated on the gold rod, and more gold surfaces as reaction sites are blocked from contacting the reaction solution. Therefore, compared with the hot dog shape, the area of cuprous oxide coating on the gold rod in the hammer shape and dumbbell shape is smaller, the density of electron-hole recombination at the interface is less, and the charge separation effect of the Schottky effect is better. Moreover, the dumbbell shape has a higher density of Schottky junctions than the hammer shape (the ratio is 2:1), and the photocurrent is the strongest;
[0028] Compared with the core-shell structure, the Janus structure decays faster, which may be due to the spatial separation of the gold rod and cuprous oxide, resulting in better charge separation. The decay lifetimes of the three Janus structures decrease in the order of hot dog shape, hammer shape, and dumbbell shape, which is consistent with the trend of the photocurrent;
[0029] Fig.14 The photocurrent curve test diagrams of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold ball / cuprous oxide Janus structure. The photocurrent ratio of the gold ball / cuprous oxide Janus structure, the gold rod / cuprous oxide core-shell structure, and the dumbbell-shaped gold rod / cuprous oxide Janus structure is 8:9:30. The contribution of the surface plasmon resonance of the gold rod should be the reason for the photocurrent enhancement ( Fig.11 );
[0030] Photodegradation test diagram of methyl orange of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold ball / cuprous oxide Janus structure. The photocatalytic efficiency is: dumbbell-shaped gold rod / cuprous oxide Janus structure>gold rod / cuprous oxide core-shell structure>gold ball / cuprous oxide Janus structure. Among them, for the gold rod / cuprous oxide core-shell structure, the photocatalytic degradation rate of methyl orange is 88% when the reaction is 2h. For the dumbbell structure, the same degradation rate was achieved within a reaction time of 60min. That is, the photocatalytic efficiency of the dumbbell structure is at least twice that of the core-shell structure, which is consistent with the trend of photocurrent generation and transient absorption measurement. The physical separation of the gold rod and cuprous oxide in the dumbbell structure enhances charge separation, which is the reason for its improved performance. The gold ball / cuprous oxide Janus structure has the lowest photocatalytic degradation efficiency for methyl orange. This may be due to the stronger plasma resonance absorption of the gold rod, which enhances the utilization of light in the visible light range ( Fig.11 ); BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Figure 1 This is a SEM image of the hot dog-shaped gold rod / cuprous oxide Janus structure prepared in Example 1;
[0033] Figure 2 TEM and SEM images of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2;
[0034] Figure 3 This is a SEM image of the hammer-shaped gold rod / cuprous oxide Janus structure prepared in Example 3;
[0035] Figure 4 TEM image of the dumbbell-shaped gold rod / cuprous oxide Janus structure with a cuprous oxide edge size of 46 nm prepared in Example 4;
[0036] Figure 5 TEM image of the dumbbell-shaped gold rod / cuprous oxide Janus structure with a cuprous oxide edge size of 52 nm prepared in Example 5;
[0037] Figure 6 TEM image of a dumbbell-shaped gold rod / cuprous oxide Janus structure with an aspect ratio of 6 prepared in Example 6;
[0038] Figure 7 TEM image of the gold rod / cuprous oxide core-shell structure prepared in Example 7;
[0039] Figure 8 HAADF-STEM image and electron energy spectrum elemental surface scan of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2.
[0040] Fig. 9 This is the XPS spectrum of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2. Fig.10 SEM image of gold sphere / cuprous oxide synthesized by the method of our previous work (Angew. Chem. Int. Ed. 2020, 59, 22246-22251);
[0041] Fig.11 Absorption spectra of gold spheres and gold rods used to synthesize gold sphere / cuprous oxide Janus structures and gold rod / cuprous oxide Janus structures (TSPR: transverse absorption peak, LSPR: longitudinal absorption peak).
[0042] Fig.12Photocurrent it curve test graphs of the hot dog-shaped (b), dumbbell-shaped (c), and hammer-shaped (d) gold rod / cuprous oxide Janus structures prepared in Examples 1, 2, and 3, and the gold rod / cuprous oxide core-shell structure (a) prepared in Example 7.
[0043] Fig.13 These are transient fluorescence test graphs of the hot dog-shaped, dumbbell-shaped, and hammer-shaped gold rod / cuprous oxide Janus structures prepared in Examples 1, 2, and 3, and the gold rod / cuprous oxide core-shell structure prepared in Example 7.
[0044] Fig.14 The photocurrent it curve test diagrams of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold sphere / cuprous oxide Janus structure.
[0045] Fig.15 These are test diagrams of photodegradation of methyl orange of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold sphere / cuprous oxide Janus structure. DETAILED DESCRIPTION
[0046] Example 1: A method for preparing a gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies, comprising the following steps:
[0047] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0048] (2) Under high-speed vortexing, 2 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0049] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution (2mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, a gold rod / cuprous oxide hot dog-shaped Janus nanostructured material can be obtained. Figure 1This is the SEM image of the hot dog-shaped gold rod / cuprous oxide Janus structure obtained in this experiment.
[0050] Example 2: A method for preparing gold rod / cuprous oxide Janus structure nanomaterials with different morphologies, comprising the following steps:
[0051] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0052] (2) Under high-speed vortexing, 4 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0053] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution (2mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material can be obtained. Figure 2 TEM and SEM images of the hot dog-shaped gold rod / cuprous oxide Janus structure obtained in this experiment.
[0054] Figure 8 The HAADF-STEM image and electron energy spectrum elemental scan of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2. The distribution of Au, Cu, O, and S elements in the EDS scan of the structure vividly shows that the ligand is adsorbed on the gold rod. Therefore, it is inferred that the formation of the Janus structure is regulated by the thiol ligand AMBI ligand;
[0055] Fig. 9 This is the XPS spectrum of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2. The XPS spectrum shows two Cu peaks at 932.65eV and 953.50eV, which are Cu + Cu 2p3 / 2 and Cu 2p1 / 2, which proves that Cu 2 The presence of O. 532.07 eV is attributed to Cu 2 O of O 2-ions. The two peaks at 84.29eV and 87.97eV are typical spin-orbit splittings of Au 4f level. Combined with the results of electron energy spectrum element scanning, it can be inferred that the hybrid material obtained by this method is gold / cuprous oxide;
[0056] Example 3: A method for preparing gold rod / cuprous oxide Janus structure nanomaterials with different morphologies, comprising the following steps:
[0057] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0058] (2) Under high-speed vortexing, 6 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0059] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution (2mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, a hammer-shaped gold rod / cuprous oxide Janus nanostructured material can be obtained. Figure 3 This is the SEM image of the hammer-shaped gold rod / cuprous oxide Janus nanostructure obtained in this experiment.
[0060] Fig.11 The absorption spectra of gold spheres and gold rods used to synthesize gold sphere / cuprous oxide Janus structures and gold rod / cuprous oxide Janus structures (TSPR: transverse absorption peak, LSPR: longitudinal absorption peak). Gold rods have better absorption in the visible light range than gold spheres, which is beneficial to the utilization of sunlight by gold rod / cuprous oxide hybrid structure materials.
[0061] Fig.12 Photocurrent it curve test graphs of the hot dog-shaped (b), dumbbell-shaped (c), and hammer-shaped (d) gold rod / cuprous oxide Janus structures prepared in Examples 1, 2, and 3, and the gold rod / cuprous oxide core-shell structure (a) prepared in Example 7.
[0062] Compared with the gold rod / cuprous oxide core-shell structure, the gold rod / cuprous oxide hotdog-shaped, hammer-shaped, and dumbbell-shaped Janus structures all show obvious photocurrent enhancement in the ratio of 1:2:4:20, which is due to the physical separation of gold and cuprous oxide.
[0063] From the hot dog shape to the hammer shape and dumbbell shape of the Janus structure, the photocurrent shows a trend of gradual strengthening, which is most likely the influence of the strength of the Schottky effect. Gold / cuprous oxide is used as the photocathode material. The photogenerated electrons generated by cuprous oxide are transferred to the surface of the gold rod to participate in the water reduction reaction to release hydrogen. Therefore, more cuprous oxide is coated on the gold rod, and more gold surfaces as reaction sites are blocked from contacting the reaction solution. Therefore, compared with the hot dog shape, the area of cuprous oxide coating on the gold rod in the hammer shape and dumbbell shape is smaller, the density of electron-hole recombination at the interface is less, and the charge separation effect of the Schottky effect is better. Moreover, the dumbbell shape has a higher density of Schottky junctions than the hammer shape (the ratio is 2:1), and the photocurrent is the strongest;
[0064] Example 4: A method for preparing a gold rod / cuprous oxide Janus structure nanomaterial with different morphologies, comprising the following steps:
[0065] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0066] (2) Under high-speed vortexing, 4 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0067] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL cupric chloride solution (4mM), the solution of step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing for reaction at room temperature for 15min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material with a larger cuprous oxide size (the edge length of the cuprous oxide is increased from 28nm in Example 2 to 46nm) can be obtained. Figure 4 The dumbbell-shaped gold rod / cuprous oxide Janus nanostructure obtained in this experiment has a cuprous oxide edge size of 46 nm.
[0068] Example 5: A method for preparing gold rod / cuprous oxide Janus structure nanomaterials with different morphologies, comprising the following steps:
[0069] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0070] (2) Under high-speed vortexing, 4 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0071] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL cupric chloride solution (6mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing for reaction at room temperature for 15min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material with a larger cuprous oxide size (the edge length of the cuprous oxide is increased from 28nm in Example 2 to 52nm) can be obtained. Figure 5 The dumbbell-shaped gold rod / cuprous oxide Janus nanostructure obtained in this experiment has a cuprous oxide edge size of 52 nm.
[0072] Example 6: A method for preparing gold rod / cuprous oxide Janus structure nanomaterials with different morphologies, comprising the following steps:
[0073] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 120 nm, diameter 20 nm) with an aspect ratio of 6 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0074] (2) Under high-speed vortexing, 4 μL of thiol ligand AMBI (1 mM) was injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60° C. for 2 h, and then allowed to stand to room temperature;
[0075] (3) Under high-speed vortexing, add 9.45 mL of H 2O, 0.087g SDS, 0.6mL copper chloride solution (4mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material with an aspect ratio of 6 can be obtained. Figure 6 This is the dumbbell-shaped gold rod / cuprous oxide Janus nanostructure with a gold rod aspect ratio of 6 obtained in this experiment.
[0076] Example 7: A method for preparing gold rod / cuprous oxide Janus structure nanomaterials with different morphologies, comprising the following steps:
[0077] (1) According to the seed growth method described in the literature (Nano Lett. 2013, 13, 765-771), gold rods (length 80 nm, diameter 20 nm) with an aspect ratio of 4 were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the product was centrifuged twice to remove the excess surfactant CTAB, and then dispersed in the same volume of water;
[0078] (2) Incubate the 1 mL gold rod synthesized in step 1 in an oven at 60° C. for 2 h under high-speed vortex oscillation and then allow to cool to room temperature;
[0079] (3) Under high-speed vortexing, add 9.45 mL of H 2 O, 0.087g SDS, 0.6mL copper chloride solution (2mM), the solution in step 2, 0.25mL sodium hydroxide solution (1M) and 0.1mL reducing agent hydroxylamine hydrochloride solution (200mM), after standing and reacting at room temperature for 15min, the gold rod / cuprous oxide core-shell structure nanomaterial can be obtained. Figure 7 This is the TEM image of the gold rod / cuprous oxide core-shell structure obtained in this experiment.
[0080] Fig.13 Transient fluorescence test graphs of the hot dog-shaped, dumbbell-shaped, and hammer-shaped gold rod / cuprous oxide Janus structures prepared in Example 1, Example 2, and Example 3, and the gold rod / cuprous oxide core-shell structure prepared in Example 7. The excitation wavelength is 340nm, and the emission wavelength is 494nm. Compared with the core-shell structure, the Janus structure decays faster, which may be due to the spatial separation of the gold rod and cuprous oxide, and the better charge separation effect. The decay lifetimes of the three Janus structures decrease in the order of hot dog shape, hammer shape, and dumbbell shape, which is consistent with the trend of the photocurrent;
[0081] Fig.14The photocurrent curve test diagrams of the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold ball / cuprous oxide Janus structure. The photocurrent ratio of the gold ball / cuprous oxide Janus structure, the gold rod / cuprous oxide core-shell structure, and the dumbbell-shaped gold rod / cuprous oxide Janus structure is 8:9:30. The contribution of the surface plasmon resonance of the gold rod should be the reason for the photocurrent enhancement ( Fig.11 );
[0082] Fig.15 The photodegradation test diagram of methyl orange for the dumbbell-shaped gold rod / cuprous oxide Janus structure prepared in Example 2, the gold rod / cuprous oxide core-shell structure prepared in Example 7, and the gold ball / cuprous oxide Janus structure. The photocatalytic efficiency is: dumbbell-shaped gold rod / cuprous oxide Janus structure>gold rod / cuprous oxide core-shell structure>gold ball / cuprous oxide Janus structure. Among them, for the gold rod / cuprous oxide core-shell structure, the photocatalytic degradation rate of methyl orange was 88% when the reaction was 2h. For the dumbbell structure, the same degradation rate was achieved within a reaction time of 60min. That is, the photocatalytic efficiency of the dumbbell structure is at least twice that of the core-shell structure, which is consistent with the trend of photocurrent generation and transient absorption measurement. The physical separation of the gold rod and cuprous oxide in the dumbbell structure enhances charge separation, which is the reason for its improved performance. The gold ball / cuprous oxide Janus structure has the lowest photocatalytic degradation efficiency for methyl orange. This may be due to the stronger plasma resonance absorption of the gold rod, which enhances the utilization of light in the visible light range ( Fig.11 );
[0083] Finally, it should be emphasized that the concentration, volume, aspect ratio and other technical parameters mentioned in the technical solution of the invention are adjustable and are not limited by the actual parameters mentioned in this article. In addition, the above specific description of the present invention is only used to illustrate the technical solution of the present invention and is not limited to the specific examples described in the present invention. Those skilled in the art should understand that any modification or equivalent replacement of the present invention to achieve the same technical effect is within the scope of protection of the present invention.
Claims
1. A method for preparing a gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies, characterized in that: The following steps are involved: (1) Gold rods with different aspect ratios were synthesized. The final product was centrifuged at 7000 rpm for 20 min, the supernatant was removed, and the excess surfactant CTAB was removed by centrifugation twice, and then dispersed in the same volume of water. (2) Under high-speed vortexing, different volumes of 1 mM thiol ligand AMBI 5-amino-2-mercaptobenzimidazole were injected into the 1 mL gold rod synthesized in step 1, incubated in an oven at 60 °C for 2 h, and then allowed to stand to room temperature; (3) Under high-speed vortex oscillation, 9.45 mL of H2O, 0.087 g of SDS, 0.6 mL of cupric chloride solutions of different concentrations, the solution in step 2, 0.25 mL of 1 M sodium hydroxide solution, and 0.1 mL of 200 mM reducing agent hydroxylamine hydrochloride solution were added to a 20 mL reaction bottle in sequence. After standing for 15 min at room temperature, Janus nanostructured materials of different shapes of gold rods / cuprous oxide were obtained.
2. The method for preparing the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies according to claim 1, characterized in that: The molar ratio of the thiol ligand AMBI 5-amino-2-mercaptobenzimidazole to the reducing agent hydroxylamine hydrochloride is 1-3:10000.
3. The method for preparing the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies according to claim 1, characterized in that: The aspect ratio of the gold rod used in step 1 is 4-6.
4. The method for preparing the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies according to claim 1, characterized in that: The molar ratio of the cuprous oxide precursor solution to the sodium hydroxide solution is 3-9:
625.
5. The method for preparing the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies according to claim 1, characterized in that: The concentration of 1 mM thiol ligand AMBI 5-amino-2-mercaptobenzimidazole is in the range of 2 μL to 6 μL; the concentration of 0.6 mL copper chloride in step (3) is in the range of 2 mM to 6 mM.
6. The method for preparing the gold rod / cuprous oxide Janus structure nano-photocatalytic material with different morphologies according to claim 1, characterized in that: The following steps are involved: (1) Synthesize gold rods with an aspect ratio of 4, a length of 80 nm, and a diameter of 20 nm. The final product is centrifuged at 7000 rpm for 20 min, the supernatant is removed, and the product is centrifuged twice to remove excess surfactant CTAB and dispersed in the same volume of water. (2) Under high-speed vortexing, inject 4 μL of 1 mM thiol ligand AMBI 5-amino-2-mercaptobenzimidazole into the 1 mL gold rod synthesized in step 1, incubate in an oven at 60 °C for 2 h, and then let stand to room temperature; (3) Under high-speed vortex oscillation, 9.45 mL of H2O, 0.087 g of SDS, 0.6 mL of 2 mM copper chloride solution, the solution in step 2, 0.25 mL of 1 M sodium hydroxide solution, and 0.1 mL of 200 mM reducing agent hydroxylamine hydrochloride solution were added to a 20 mL reaction bottle in sequence. After standing at room temperature for 15 min, a dumbbell-shaped gold rod / cuprous oxide Janus nanostructured material was obtained.
7. The gold rod / cuprous oxide Janus structure nanomaterial prepared according to the method according to any one of claims 1 to 6.
8. The use of the gold rod / cuprous oxide Janus structure nanomaterial according to claim 7, characterized in that: Used in photocatalytic materials.
Citation Information
Patent Citations
Method for preparing gold kernel cuprous oxide shell composite nanometer structure, and composite nanometer structure
CN103934466A
Preparation method of ternary composite enhanced photocatalyst with inside-outside synergy and surface plasmon resonance effect
CN110302802A